Integrated Nutrient Management on Productivity of Carrot and Fertility of Soil - Vithwel, Dr; Kanaujia, SP (SAARC Journal of Agriculture, 2014)
No Abstract Available DOI: http://dx.doi.org/10.3329/sja.v11i2.18412 SAARC J. Agri., 11(2): 173-181 (2013)